Four-chain integration and policy pathways for marine new type productivity - Lu, Dandan; Li, Li (Frontiers in Marine Science, 2025)
This study constructs an evaluation system incorporating the four chains of talent, innovation, industry, and capital to measure marine new-quality productivity across 11 coastal provinces in China from 2011 to 2022. Using entropy weighting, kernel density estimation, and fuzzy-set Qualitative Comparative Analysis (fsQCA), the study analyzes the spatiotemporal evolution and policy-driven pathways of marine productivity. The results indicate an overall upward trend in marine productivity with significant regional disparities. High-level regions exhibit synergistic policies across the four chains, while medium- and low-level regions face constraints due to insufficient talent and capital support. The policy focus has shifted from industry-led development to innovation-capital synergy, providing empirical support for differentiated policy design to promote coordinated regional development of marine new-quality productivity.